A detailed mechanism of degradation behaviour of biodegradable as-ECAPed Zn-0.8Mg-0.2Sr with emphasis on localized corrosion attack - Pinc, Jan; Školáková, Andrea; Hybášek, Vojtěch; Msallamová, Šárka; Veřtát, Petr; Ashcheulov, Petr; Vondráček, Martin; Duchoň, Jan; McCarroll, Ingrid; Hývl, Matěj; Banerjee, Swarnendu; Drahokoupil, Jan; et al. (Bioactive materials, 2023)
In this study, advanced techniques such as atom probe tomography, atomic force microscopy, X-ray photoelectron spectroscopy, and electrochemical impedance spectroscopy were used to determine the corrosion mechanism of the as-ECAPed Zn-0.8Mg-0.2Sr alloy. The influence of microstructural and surface features on the corrosion mechanism was investigated. Despite its significance, the surface composition before exposure is often neglected by the scientific community. The analyses revealed the formation of thin ZnO, MgO, and MgCO3 layers on the surface of the material before exposure. These layers participated in the formation of corrosion products, leading to the predominant occurrence of hydrozincite. In addition, the layers possessed different resistance to the environment, resulting in localized corrosion attacks. The segregation of Mg on the Zn grain boundaries with lower potential compared with the Zn-matrix was revealed by atom probe tomography and atomic force microscopy. The degradation process was initiated by the activity of micro-galvanic cells, specifically Zn - Mg2Zn11/SrZn13. This process led to the activity of the crevice corrosion mechanism and subsequent attack to a depth of 250 μm. The corrosion rate of the alloy determined by the weight loss method was 0.36 mm·a-1. Based on this detailed study, the degradation mechanism of the Zn-0.8Mg-0.2Sr alloy is proposed.
Keywords: Mechanism; Zinc-based alloy; Characterization; Biodegradable metals; ECAP